2005
DOI: 10.4065/80.9.1177
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Vertebral Column Metastases

Abstract: The vertebral column is recognized as the most common site for bony metastases in patients with systemic malignancy. Patients with metastatic spinal tumors may present with pain, neurologic deficit, or both. Some tumors are asymptomatic and are detected during screening examinations. Treatment options include medical therapy, surgery, and radiation. However, diversity of patient condition, tumor pathology, and anatomical extent of disease complicate broad generalizations for treatment. Historically, surgery wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
24

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 86 publications
1
84
0
24
Order By: Relevance
“…The great majority of vertebral tumor lesions consist of secondary lesions, especially in adult patients (2) . Around 50% to 70% of the patients who die because of malignant neoplasia present bone metastases in the spine (2,10) .…”
Section: Discussionmentioning
confidence: 99%
“…The great majority of vertebral tumor lesions consist of secondary lesions, especially in adult patients (2) . Around 50% to 70% of the patients who die because of malignant neoplasia present bone metastases in the spine (2,10) .…”
Section: Discussionmentioning
confidence: 99%
“…These clinical representations of spinal metastasis seem to be correlated with the pathophysiology of the spinal metastasis described in the past (4). Therefore, we propose two learning objectives in our study.…”
Section: Introductionmentioning
confidence: 94%
“…Spinal metastasis can occur in three regions including the extradural, intradural extramedullary, and intramedullary regions (4). As most spinal metastases (more than 98%) occur in an extradural location, anatomical classification of the extradural location is very important (8).…”
Section: Anatomical Classificationsmentioning
confidence: 99%
“…Therefore, a posterior-alone procedure without any anterior augmentation, may carry the risk of worse clinical and radiological outcome through the follow-up [24]. Sundaresan et al described 101 consecutive patients suffering from cervical, thoracic, and lumbar metastasis with anterior vertebral body resection and stabilization with methyl methacrylate and Steinmann pins, and they reported that additional augmentation using posterior instrumentation was required for 10% of them [16,17].…”
Section: Figurementioning
confidence: 99%